THU0288 LONG-TERM FOLLOW-UP OF ANTI-IL6-RECEPTOR TOCILIZUMAB IN REFRACTORY UVEITIS IN PATIENTS WITH BEHÇET'S DISEASE. MULTICENTER STUDY OF 14 PATIENTS IN CLINICAL PRACTICE. (June 2019) - Atienza-Mateo, Belén; Martín-Varillas, José Luis; Calvo-Río, Vanesa; Demetrio-Pablo, Rosalía; Palmou-Fontana, Natalia; Loricera, J.; Beltrán, Emma; Hernández-Garfella, Marisa; Martinez-Costa, Lucía; Valls-Pascual, Elia; Atanes-Sandoval, Antonio; Cordero-Coma, Miguel; et al.
Abstract : Background: Ocular involvement in Behçet's disease (BD) is a potential severe and disabling complication. Anti-TNF-α agents have shown an improvement of visual outcome in BD-related uveitis refractory to conventional immunosuppressive (IS) drugs. However, these drugs do not achieve control of intraocular inflammation in all patients or are not well tolerated. Tocilizumab (TCZ) has shown efficacy in different refractory ocular inflammatory diseases. Objectives: To assess the efficacy of long-term therapy with TCZ in refractory uveitis associated to extraocular manifestations (EOM) due to BD. Methods: Multicenter study of patients with BD refractory to standard systemic treatment. Results: We followed up 14 patients (9 men/5 women) (26 affected eyes); mean age 40.8±19.5 years. Pattern of ocular involvement: panuveitis (10; 4 with retinal vasculitis), anterior (3) and posterior (1) uveitis; 8 recurrent and 6 chronic; 9 with cystoid macular edema. At TCZ onset the following EOM were present: oral and/or genital ulcers (10), arthritis (6), folliculitis/pseudofolliculitis (6), erythema nodosum (3), livedo reticularis (1), intestinal affection (1) and neurological involvement (3). Before TCZ, they had received corticosteroids (13 intraocular, 12 oral and 12 iv), conventional IS drugs and biologic agents: methotrexate (11), cyclosporine (8), azathioprine (10), colchicine (1), cyclophosphamide (2), mycophenolate mofetil (1), adalimumab (10), infliximab (6), golimumab (3), canakinumab (1), or etanercept (1). TCZ was used in monotherapy (7) or combined with conventional IS drugs (7) at 8 mg/kg/iv/4 w (11) or 162 mg/sc/w (3). After a mean follow-up of 21.7±14.5 months using TCZ, all patients experienced ocular improvement, with complete remission in 10. However, TCZ was only effective in 5 of the patients with EOM. TABLE shows the evolution of ocular parameters. TCZ had to be withdrawn temporally in 1 case, due to an episode of cellulitis with sepsis, and definitely in 4 cases, due to a severe infusion reaction, arthritis impairment, persistence of oral ulcers or a new episode of uveitis (1 each). Prednisone dose was significantly reduced until suspension in all patients. Conclusion: TCZ seams a useful and secure therapy in highly refractory BD-related uveitis. References: [1] Atienza-Mateo B, Calvo-Río V, Beltrán E, et al. Anti-interleukin 6 receptor tocilizumab in refractory uveitis associated with Behçet's disease: multicentre retrospective study. Rheumatology (Oxford). 2018 May 1;57(5):856-864. [2] Calvo-Río V, de la Hera D, Beltrán-Catalán E, et al. Tocilizumab in uveitis refractory to other biologic drugs: a study of 3 cases and a literature review. Clin Exp Rheumatol.2014; 32(4 Suppl 84): S54-7. Disclosure of Interests: Belén Atienza-Mateo: None declared, José Luis Martín-Varillas: None declared, Vanesa Calvo-Río: None declared, Rosalía Demetrio-Pablo: None declared, Natalia Palmou-Fontana: None declared, J. Loricera: None declared, Emma Beltrán: None declared, Marisa Hernández-Garfella: None declared, Lucía Martinez-Costa: None declared, Elia Valls-Pascual: None declared, Antonio Atanes-Sandoval: None declared, Miguel Cordero-Coma: None declared, Joan Miquel Nolla: None declared, Carmen Carrasco-Cubero: None declared, Julio Sánchez: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Lara Sánchez Bilbao: None declared, Iñigo González-Mazón: None declared, Monica Calderón-Goercke: None declared, D. Prieto-Peña: None declared, Miguel Á. González-Gay: None declared, Ricardo Blanco: None declared